1. since the equations equal each other
2x+19=x+7
-x -x
x+19=7
-19 -19
x= -12
sub into y= x+7
y= -12+7
y= -5
2. x+2y=-7
<span>x+y+23=0
i don't know what the second equation is equal to, i'll assume 0
2y=x-7
y=1/2x-7/2
sub this into x+y+23=0
x+1/2x-7/2+23=0
3/2x+39/2=0
-39/2 -39/2
3/2x= -39/2
x=-39/2 / 3/2
x= -13
sub into y=1/2x-7/2
y=1/2(-13)-7/2
y= -10
3. </span>x+5y=2
<span>x=-4y+5
</span>sub x=-4y+5 into x+5y=2
-4y+5+5y=2
y+5=2
-5 -5
y= -3
sub y =-3 into x =-4y+5
x=-4(-3)+5
x= 17
4. 3x+y=9
<span>y=-5x+9
</span>sub -5x+9 into 3x+y=9
3x+(-5x+9)=9
3x-5x+9=9
-2x+9=9
-9 -9
-2x=0
x=0
sub into y=-5x+9
y=-5(0)+9
y=9
Answer:
Step-by-step explanation:
- Speed in one direction = 40 km/h
- Speed on return = x
- Average speed = 60 km/h
Let the distance be d
<u>Average speed </u>
- 2d/(d/40 + d/x) = 60
- d/40 + d/x = 2d/60
- 1/40 + 1/x = 1/30
- 1/x = 1/30 - 1/40
- 1/x = (4-3)/120
- 1/x = 1/120
- x = 120 km/h
Final Result :
x - 3y
Processing ends successfully
Answer:
89
Step-by-step explanation:
Answer:
<h2>
<em>(</em><em>4</em><em>,</em><em>5</em><em>)</em></h2>
<em>sol</em><em>ution</em><em>,</em>
<em>A</em><em>(</em><em>2</em><em>,</em><em>7</em><em>)</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>></em><em> </em><em>(</em><em>X1,</em><em>y1</em><em>)</em>
<em>B</em><em>(</em><em>6</em><em>,</em><em>3</em><em>)</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>></em><em>(</em><em>x2</em><em>,</em><em>y2</em><em>)</em>
<em>now</em><em>,</em>
<em>
</em>
<em>hope</em><em> </em><em>this</em><em> </em><em>helps</em><em>.</em><em>.</em><em>.</em>
<em>Good</em><em> </em><em>luck</em><em> on</em><em> your</em><em> assignment</em><em>.</em><em>.</em><em>.</em>